2017
DOI: 10.1159/000481571
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine Causes Lipolysis and Apoptosis in Adipocytes through the Tumor Necrosis Factor Alpha-Dependent Pathway

Abstract: A phosphatidylcholine (PPC) formulation has been used to treat cellulite; however, its underlying mechanism of action remains unclear. In this study, we demonstrated that PPC induces lipolysis and apoptosis in adipocytes, and evaluated a possible tumor necrosis factor alpha (TNFα)-dependent pathway, whereby PPC exerts these effects. For in vitro study, fully differentiated 3T3-L1 cells, mouse adipocytes were treated with various concentrations of PPC and cell apoptosis and lipolysis were assayed. For in vivo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…[95][96][97] Adipokines such as leptin and TNF-α mediate apoptosis through caspase-dependent pathways and regulate body fat mass. 98,99 In addition, a variety of natural compounds, including xanthohumol, isoxanthohumol and ajoene, have been reported to induce apoptosis in adipocytes. 100,101 Interestingly, these compounds have been independently studied for their anti-obesity effects, 102,103 which means that the anti-obesity effects of some natural compounds may be achieved by inducing the brown fat-like phenotype and apoptosis of white adipocytes.…”
Section: Hydrogen Sulfide and Adipocytes Apoptosismentioning
confidence: 99%
“…[95][96][97] Adipokines such as leptin and TNF-α mediate apoptosis through caspase-dependent pathways and regulate body fat mass. 98,99 In addition, a variety of natural compounds, including xanthohumol, isoxanthohumol and ajoene, have been reported to induce apoptosis in adipocytes. 100,101 Interestingly, these compounds have been independently studied for their anti-obesity effects, 102,103 which means that the anti-obesity effects of some natural compounds may be achieved by inducing the brown fat-like phenotype and apoptosis of white adipocytes.…”
Section: Hydrogen Sulfide and Adipocytes Apoptosismentioning
confidence: 99%
“…At the same time, PE and PC metabolize diacylglycerol, fatty acid, and phospholipid acid as second messengers, which play important roles in the cell signal conduction process (Momchilova and Markovska 1999). Jung et al (2018) found that, in vivo experiments, when PC was injected twice into subcutaneous adipose tissue in mice, fed a high-fat diet for 8 weeks, it induced adiposysis and apoptosis in a dosedependent manner in fully differentiated 3T3-L1 cells. PCinduced lipolysis and apoptosis in adipocytes could be related to TNFα-dependent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics can also help classify cells according to their molecular characteristics, identify metabolite biomarkers in biological samples, and evaluate the effects of different drugs on cells and tissues (Panopoulos et al 2012;Armitage and Barbas 2014). Studies have made significant progress in understanding the regulation of metabolism, especially the interaction between growth control, differentiation, signaling pathways, and metabolism (Yuan et al 2013;Jung et al 2018). Furthermore, many studies have found relative availability of amino acids, nitrates, sugars, and lipid metabolism regulation as metabolic intermediates as epigenetic modification cofactors (Harvey et al 2016;Lees et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Injection lipolysis with deoxycholic acid (ATX‐101) respectively phosphatidylcholine (compounds) induce lipolysis and apoptosis dose‐dependently in adipocytes through mainly TNFα‐dependent pathways (Jung et al, ). Deoxycholic acid is the first pharmaceutical therapy approved by the FDA for the reduction in submental fat and has been intensively investigated in multiple trials (Wollina & Goldman, ).…”
Section: The Adipose Tissue In Body Contouringmentioning
confidence: 99%
“…Body contouring is a method to improve body shape and correct local- (Jung et al, 2018). Deoxycholic acid is the first pharmaceutical therapy approved by the FDA for the reduction in submental fat and has been intensively investigated in multiple trials (Wollina & Goldman, 2015).…”
Section: The Adipose Tissue In Body Contouringmentioning
confidence: 99%